Institutions and Financial Development: Evidence from International Migrants in the United States - Osili, Una Okonkwo; Paulson, Anna L. (The Review of Economics and Statistics, 2008)
We investigate the impact of institutions on financial development by analyzing the financial behavior of immigrants in the United States. We find that immigrants from countries with institutions that more effectively protect private property are more likely to own stock in the United States. The effect of home-country institutions is persistent and absorbed early in life. The impact of institutions is amplified for immigrants who live in metropolitan areas with many other immigrants from the same country. These findings are robust to alternative measures of institutional effectiveness and to various methods of controlling for unobserved individual characteristics, including specifications with country fixed effects.